Determination of Antioxidant Activity of Jeruasalem Artichoke (Helianthus Tuberosus L.) Plant - Abdullajonova Yulduzkhon Uchkun qizi, (American Journal of Biology and Natural Sciences, 2025)
In this article, the chemical composition and the antioxidant activity of the root fruit extract of the jerusalem artichoke (Helianthus tuberosus L) grown in Uzbekistan are studied. As a result of the analysis, the antioxidant activity of the sample is determined by the inhibition of the autoxidation reaction of adrenaline in vitro, until the free form of oxygen is formed prevented.